Lessons learned from a cancer knowledge translation grants program: results of an evaluation. - O’Brien, M. A.; Makuwaza, T.; Graham, I. D.; Barbera, L.; Earle, C. C.; Brouwers, M. C.; Grunfeld, E. (Current Oncology, 2019)
Background A novel way to build capacity in knowledge translation (KT) is through KT-focused grant competitions. Since 2009, the Knowledge Translation Research Network (KT-Net) has had a cancer-related KT grants program. We undertook an evaluation of the program to determine if KT-Net was achieving its aims of building capacity in cancer KT, advancing the science of KT, building partnerships, and leveraging funding. Methods An adapted framework guided the evaluation. Nine funded studies from 4 competitions were included. Semi-structured telephone interviews were held with researchers, stakeholders (including knowledge users), members of grant review panels, and experts in KT. Interview transcripts were audio-recorded, transcribed, and analyzed thematically. A review of proposal and report documents was also conducted. Results Funded researchers indicated that the grant competition was an essential funding program for cancer KT research. Competitions were perceived to build capacity in cancer KT among early-career researchers and to encourage innovative cancer KT research for which alternative funding sources are limited. The grants program resulted in incremental gains in advancing the science of KT. Suggestions to improve the program included stronger partnerships between the funder and the provincial cancer-system organization to optimize the application of research that is relevant to the organization’s strategic objectives. Conclusions The grants program met many of its aims by providing cancer researchers with an opportunity to gain capacity in cancer KT and by making incremental advances in KT science. Suggestions to improve the program included closer partnerships between the funder and the cancer-system organization.